ESG and Technology Investment: Evidence of Their Synergistic Effect on Corporate Valuation - Muh Havid Al Badar; Muhammad Saiful Hakim (Information Technology and Science (ITScience), 2026)
This study examines the individual and synergistic effects of digital technology application, represented by information technology capital expenditure (Capex IT), and Environmental, Social, and Governance (ESG) performance on corporate valuation, measured using Tobin’s Q. The analysis investigates whether technology investment and sustainability performance operate as complementary strategic drivers of firm value. The empirical results indicate that Capex IT exhibits a consistently positive and statistically significant influence on corporate valuation, suggesting that technology-related investments enhance operational efficiency, competitive advantage, and market expectations of future growth. In contrast, ESG performance demonstrates a negative and significant relationship with Tobin’s Q across several baseline model specifications, implying that ESG initiatives may not yet be fully priced by the market or may involve short-term costs that outweigh perceived benefits. However, when ESG is decomposed into its environmental, social, and governance components and included simultaneously, the aggregate ESG effect becomes positive and significant, indicating that a more balanced and integrated sustainability structure contributes to value creation. Moreover, the interaction term between Capex IT and ESG Score reveals a positive and significant effect on firm value, providing strong evidence of a synergistic relationship. This finding suggests that digital technology investment enhances the effectiveness, transparency, and market relevance of ESG initiatives. Overall, the results highlight the role of technological capability as a critical enabler that amplifies the value relevance of sustainability performance, offering important implications for managers and investors seeking to integrate digital transformation and ESG strategies to strengthen long-term corporate valuation.